Defending the leaf surface: intra- and inter-specific differences in silicon deposition in grasses in response to damage and silicon supply - Hartley, Sue E.; Fitt, Rob N.; McLarnon, Emma L.; Wade, Ruth N. (Frontiers in Plant Science, 2015)
Understanding interactions between grasses and their herbivores is central to the conservation of species-rich grasslands and the protection of our most important crops against pests. Grasses employ a range of defenses against their natural enemies; silicon-based defenses have been shown to be one of the most effective. Silicon (Si) is laid down on the leaf surface as spines and other sharp bodies, known as phytoliths, making grasses abrasive and their foliage indigestible to herbivores. Previous studies on Si defenses found that closely related species may have similar levels of Si in the leaves but differ markedly in abrasiveness. Here we show how the number, shape and distribution of Si-rich phytoliths and spines differ within and between different grass species and demonstrate that species also differ in their ability to change the deposition and distribution of these defenses in response to damage or increases in Si supply. Specifically, we tested the response of two genotypes of Festuca arundinacea known to differ in their surface texture and 3 different grass species (F. ovina, F. rubra and Deschampsia cespitosa) differing in their abrasiveness to combined manipulation of leaf damage and Si supply. F.arundinacea plants with a harsh leaf surface had higher Si content and more spines on their leaf surface than soft varieties. F. ovina and D. cespitosa plants increased their leaf Si concentration and produced an increase in the number of leaf spines and phytoliths on the leaf surface in response to Si addition. F rubra also increased leaf Si content in response to treatments, particularly in damaged leaves, but did not deposit this in the form of spines or increased densities of phytoliths. We discuss how the form in which grasses deposit Si may affect their anti-herbivore characteristics and consider the ecological and agricultural implications of the differences in allocation to Si-based defenses between grass species.